Utilization of pineapple agroindustrial residue submitted to the drying process for the elaboration of cereal bars (Research, Society and Development, 2021)
The pineapple is a fruit widely cultivated in the world, however its industriais processing generates waste, where these still contain relevant nutrients. The present work aimed to study the use of pineapple residue submitted to the drying process to obtain powder and develop cereal bars. To obtain the powder the residue was submitted to the convective drying process, performing the drying kinetics and the adjustment of mathematical models to the experimental data. It was verified that all models fitted well to the experimental data, with Page's model being considered the best to represent the drying process. After the addition of the powder in the formulations of cereal bars it was verified that a higher concentration in relation to the standard bar, being that the formulation B3 with 4.5% of powder of the pineapple agroindustrial residue was the best, while the others did not differ. As for the instrumental firmness parameter, the applied force did not differ significantly at the 5% level in the standard formulations and with the addition of pineapple agroindustrial residue powder, and all the colorimetric results obtained were positive, indicating a tendency of color more towards red and yellow. As for the quantification of the compounds, the powder presented higher concentrations, catechin being the main compound. Thus, it is possible to verify the efficiency of the addition of pineapple residue powder in the enrichment of cereal bars in relation to its composition of bioactive compounds and antioxidant activity, promoting the obtaining of a cereal bar with functional properties.